The hermeneutic self: Sartre and philosophical hermeneutics - Lim, Wan Ting (Nanyang Technological University, 2022)
Currently, few scholars have drawn links between hermeneutics and Sartre. However, this area of research might be interesting as many Sartrean concepts can be clarified and reinterpreted through hermeneutical concepts. Hence, this paper aims to explore the relation between early Sartrean thought and hermeneutics in two main ways:(1) to advance the notion that early Sartrean thought does have strong ties tohermeneutics,(2) to explore how Sartre’s conception of the self can be reinterpreted through hermeneutical concepts and the implications of this reinterpretation. This paper will mainly focus on the major ideas of Heidegger and Gadamer and will attempt to start a conversationbetween them and early Sartrean ideas.